High-performance ethylene propylene diene monomer foaming material and preparation method thereof
By performing multiple modification techniques on the red brick powder, it is evenly dispersed in the EPDM foaming material, solving the problems of uneven cell cells, decreasing strength, flammability and filler agglomeration of traditional EPDM foaming materials, and the optimization of the mechanical properties, flame retardancy and dimensional stability of the material is achieved.
Patent Information
- Application Number
- CN202510190039.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-20
AI Technical Summary
Traditional EPDM foaming materials have problems of uneven cell structure, decreased strength, flammability and filler agglomeration, which affects their mechanical properties, flame retardancy and dimensional stability.
By performing multiple modifications of the red brick powder, including acid treatment and high-temperature calcination, silane coupling modification, polydopamine coating and layered double hydroxide composite modification, its dispersion and compatibility in the EPDM matrix are improved, thereby optimizing the performance of the EPDM foamed material.
It significantly improves the mechanical properties, flame retardant properties, cell structure stability and wear resistance of the material, making it more suitable for high-performance seals, rail transit and industrial shock absorbing materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer composite materials, and specifically relates to an EPDM foam material based on modified red brick powder and a preparation method thereof. The present invention performs multiple modifications on red brick powder to improve its dispersibility, compatibility and reinforcing effect in an EPDM matrix, thereby optimizing the mechanical properties, flame retardancy, pore structure and wear resistance of the EPDM foam material, making it widely applicable to high-performance rubber products such as automotive seals, rail transit sealing pads, industrial cushioning materials, soles, and shock-absorbing rubber. Background Art
[0002] Ethylene propylene diene monomer (EPDM) is widely used in automotive seals, rail transit gaskets, shock-absorbing materials, industrial cushioning materials, and shoe soles due to its excellent weather resistance, heat resistance, chemical corrosion resistance, and elasticity. However, there are still some problems with traditional EPDM foaming materials: due to the molecular structure of EPDM itself, it is easy to have uneven pore structure and reduced strength after foaming, resulting in reduced wear resistance, tear strength, and service life of the material; at the same time, EPDM is mainly composed of carbon and hydrogen elements, and its own oxygen index is low, which is easy to burn and difficult to meet the requirements of certain high safety standards (such as rail transit, building sealing, etc.); in addition, traditional inorganic fillers (such as carbon black and calcium carbonate) are easy to agglomerate in the rubber matrix, resulting in uneven stress distribution inside the material, affecting the final mechanical properties and dimensional stability.
[0003] In response to the above problems, in recent years, researchers have tried to use nanofillers, functional fillers and optimize the foaming process to improve the comprehensive performance of EPDM foam materials. Among them, the high-value utilization of construction waste has become a research hotspot. Red brick powder (MBP) is a common construction waste. Its main components are silicate, aluminum oxide and iron oxide, which have certain mechanical reinforcement and filling effects. However, the unmodified red brick powder has low surface activity and poor compatibility with EPDM. Direct addition will reduce the material performance. Therefore, how to effectively functionalize the red brick powder so that it has both mechanical reinforcement, flame retardant modification and pore control functions, and achieve the performance optimization of EPDM foam materials has become an important research direction in this field.
[0004] The present invention uses multiple modification technologies, namely silane coupling agent modification + polydopamine (PDA) coating + layered double hydroxide (LDH) composite modification, to give red brick powder higher compatibility and functionality, so that it can be evenly dispersed in EPDM foaming materials, and significantly improve the mechanical properties, flame retardant properties and pore structure stability of the material, thereby expanding its application in high-performance seals, rail transit, industrial shock-absorbing materials and other fields. Summary of the invention
[0005] The present invention provides a high-performance ethylene propylene diene monomer (EPDM) foam material based on modified red brick powder and a preparation method thereof, aiming to improve the mechanical properties, flame retardancy, pore structure stability and wear resistance of the EPDM foam material, and expand its application in high-performance rubber products such as automobiles, rail transit, and industrial cushioning materials.
[0006] To achieve the above object, the present invention adopts the following technical solution: A high-performance EPDM rubber foam material based on modified red brick powder is prepared from the following raw materials in parts by weight: 100 parts of EPDM rubber, Carbon black 10-40 parts, 40 parts of modified red brick powder, 30-50 parts of light calcium carbonate, 10-20 parts of paraffin oil, Zinc oxide 5-15 parts, Vulcanizing agent 0.5-3 parts, Accelerator 0.5-2 parts, 1-5 parts of stearic acid, Lubricant 0.5-3 parts, 5-15 parts of foaming agent.
[0007] In the present invention, the ethylene propylene diene monomer (EPDM) can be selected from high-strength and high-resistance EPDM materials, including ExxonMobil Vistalon 7500, Dow Nordel IP 4820, Lanxess Keltan 6950 and South Korea Kumho KEP 270. These EPDM materials have a high ethylene content (50% to 70%), provide higher crystallinity and mechanical strength, and have better performance in high-load, wear-resistant, tear-resistant and other application scenarios. Among them, Keltan 6950 has a high cross-linking density and good dynamic mechanical properties, and is suitable for sealing gaskets, shock-absorbing components, industrial buffer materials and other fields.
[0008] In the present invention, the BET specific surface area of the carbon black is 60-120 m 2 / g, particle size 20-40nm, to ensure the stability of the material in high-load applications. The carbon black is selected from Cabot Vulcan N330 and Degussa Printex G, among which N330 has the characteristics of high structure and high reinforcement, which can effectively improve the wear resistance, tear strength and thermal conductivity of EPDM foaming materials.
[0009] In the present invention, the paraffin oil can be selected from Chevron Paralux 6001, Sunpar 150, and NYNAS Nytex 840. Such high-viscosity mineral oils can improve the fluidity of EPDM composite materials, optimize the dispersion of fillers, and enhance the anti-aging properties of the final product. The kinematic viscosity of the paraffin oil at 40° C. is controlled at 20-60 cSt to ensure good plasticity during processing.
[0010] In the present invention, zinc oxide (ZnO) is used as a vulcanization activator and an anti-aging agent to optimize the cross-linking structure of EPDM and improve the weather resistance and fatigue resistance of the material.
[0011] In the present invention, the vulcanizing agent is selected from at least one of sulfur and BIBP.
[0012] In the present invention, the accelerator is selected from at least one of zinc dibenzyl dithiocarbamate (ZBEC), tetrabenzyl thiuram disulfide (TBZTD), and zinc diethyl dithiocarbamate (ZDEC). TBZTD can increase the crosslinking density and improve the wear resistance and dynamic properties of the material, while ZDEC can optimize the processing performance and keep the material in good flexibility during high temperature vulcanization.
[0013] In the present invention, the stearic acid is used to improve the processing properties of rubber and enhance the dispersibility of fillers.
[0014] In the present invention, the lubricant is polyethylene glycol.
[0015] In the present invention, the foaming agent is selected from at least one of 4,4'-oxybisbenzenesulfonylhydrazide (OBSH) and azodicarbonamide (AC). A composite combination of OBSH and AC is preferred to optimize the foaming rate, improve the stability of the cells, and reduce the collapse of the cells.
[0016] In the present invention, the modified red brick powder is a functional modification of construction waste red brick powder to improve its dispersibility and compatibility in the EPDM matrix, and the specific steps are as follows: (a) Acid treatment and high-temperature calcination: The red brick powder (MBP) was added to a hydrochloric acid solution with a mass concentration of 3% and stirred for 30 minutes. After washing with water to remove impurities, the powder was calcined at a high temperature of 500-800°C for 2 hours, then washed with water, filtered, and dried at 100°C for 4 hours to obtain a porous red brick powder (P-MBP) with a large specific surface area. (b) Silane coupling modification: Take the porous red brick powder, add it into anhydrous ethanol, and add the silane coupling agent Si-69, then stir it at 80°C for 1-2 hours, filter it, and obtain the silane-modified red brick powder (Si-MBP); (c) Polydopamine (PDA) coating: The obtained silane-modified red brick powder was added to a Tris-HCl buffer solution at pH = 8.5, and a 2 mg / mL dopamine (DA) solution was added, and the mixture was stirred for 12 hours to allow dopamine to self-polymerize and coat the surface of the red brick powder to obtain a red brick powder coated with polydopamine (PDA-Si-MBP); (d) Layered double hydroxide (LDH) composite modification: Take the red brick powder coated with polydopamine, add it to the MgAI-LDH suspension with a mass concentration of 2-3%, ultrasonically disperse it for 20 minutes, filter it, and vacuum dry it at 80°C for 4 hours to obtain the modified red brick powder (LDH-PDA-Si-MBP).
[0017] The red brick powder in step (a) has a BET specific surface area of 30-80 m / g and a particle size of 20-50 μm, and has a high reinforcing capacity, and can improve the wear resistance, tear strength and dimensional stability of the material.
[0018] The mass ratio of the porous red brick powder to the silane coupling agent Si-69 used in step (b) is 10:1.
[0019] The amount of dopamine solution used in step (c) is calculated by adding 10 mL per gram of silane-modified red brick powder.
[0020] The amount of MgAl-LDH suspension used in step (d) is calculated by adding 3 mL per gram of red brick powder coated with polydopamine.
[0021] The present invention treats the waste red brick powder of construction with acid and calcines it at high temperature, so as to enhance its filling capacity and load performance; improves the interface bonding force between P-MBP and EPDM by modifying the performance of coupling agent, and enhances the dispersibility and mechanical reinforcement effect of the filler in the rubber matrix; forms a uniform functional coating on the surface of Si-MBP by utilizing the adhesion property of PDA, so as to improve the uniform dispersibility and interface compatibility of the filler, and further enhance the tensile strength, wear resistance and tear strength of the material; and loads a layered double hydroxide (LDH) nanosheet layer on the surface of the PDA-coated filler, so as to optimize the gas release rate, synchronize the foaming process with the vulcanization, improve the uniformity of the pores, and reduce the size shrinkage, thereby improving the flame retardancy, thermal stability and antioxidant ability of the material.
[0022] The preparation method of the high-performance EPDM rubber foam material comprises the following steps: 1) First, vacuum dry the modified red brick powder at 80-120°C for 2-4 hours to remove the adsorbed moisture, so as to improve its dispersibility in the EPDM matrix; 2) Place the EPDM in an open mixer or internal mixer and plasticize it at 60-90°C for 3-5 minutes to achieve a suitable plastic state; 3) Add carbon black, light calcium carbonate, zinc oxide, stearic acid, paraffin oil, lubricant and dried modified red brick powder to the plasticized EPDM in sequence, and mix at 80-100°C for 8-12 minutes to evenly disperse the filler; 4) After the materials are fully mixed, cool to 50-70°C, then add accelerator, vulcanizer and foaming agent, and continue mixing at 60-80°C for 5-8 minutes to ensure uniform reaction; 5) placing the rubber mixture obtained in step 4) in a two-roll open mill for secondary plastication, and performing multiple opening and closing operations to remove gas generated during the mixing process and improve foaming uniformity; 6) Placing the rubber mixture obtained in step 5) in a mold for vulcanization and foaming to obtain the high-performance EPDM rubber foam material.
[0023] Furthermore, in step 5), the temperature of the secondary plasticizing is 40-60° C. and the time is 10-15 min.
[0024] Furthermore, in step 6), the vulcanization foaming is carried out by gradually increasing the temperature at a rate of 2-3°C / min, increasing the temperature to 155°C and keeping the temperature for 25 minutes to reduce the risk of collapse of the pore structure.
[0025] Furthermore, the vulcanization process may adopt microwave assisted vulcanization (MW-V) or conventional thermal vulcanization (CV) process to optimize the vulcanization cross-linking efficiency and improve the comprehensive performance of the material.
[0026] The prepared high-performance EPDM rubber foam material can be used for highly wear-resistant and antistatic rubber products, and is suitable for tires, soles, conveyor belts, sealing rings and rail transportation fields.
[0027] The beneficial effects of the present invention are: (1) Improving mechanical properties and increasing the service life of materials: PDA functional modification of red brick powder can enhance the interfacial bonding between it and EPDM, significantly improve the tensile strength, tear strength and elongation at break of the material, improve wear resistance and fatigue resistance, and make it more suitable for high wear resistance and impact resistance applications (such as tires, conveyor belts, and soles); at the same time, its uniform dispersion in EPDM is also improved, which can make the material less likely to break under long-term stress conditions, thereby extending the service life of the product.
[0028] (2) Optimize flame retardant properties and improve material safety: The LDH flakes introduced into the modified red brick powder can intercalate into the EPDM matrix and have a synergistic flame retardant effect, which can effectively increase the oxygen index (LOI), reduce the burning rate of the material, and improve its fire resistance. In application fields such as rail transit and building sealing, reducing the heat release rate (HRR) can effectively reduce heat accumulation during a fire and improve the flame retardant grade of the material.
[0029] (3) Optimize the cell structure and improve dimensional stability: The use of porous red brick powder can improve the foaming structure, make the cells evenly distributed, avoid collapse, and improve the resilience and dimensional stability of the material, making it suitable for high-precision seals and cushioning materials. Exhaust optimization and secondary vulcanization process can further stabilize the cell structure, so that the material maintains good elasticity and density stability after being compressed and used for a long time. DETAILED DESCRIPTION
[0030] A high-performance EPDM rubber foam material based on modified red brick powder is prepared from the following raw materials in parts by weight: 100 parts of EPDM rubber, Carbon black 10-40 parts, 40 parts of modified red brick powder, 30-50 parts of light calcium carbonate, 10-20 parts of paraffin oil, Zinc oxide 5-15 parts, Vulcanizing agent 0.5-3 parts, Accelerator 0.5-2 parts, 1-5 parts of stearic acid, Lubricant 0.5-3 parts, 5-15 parts of foaming agent.
[0031] The vulcanizing agent is selected from at least one of sulfur and BIBP. The accelerator is selected from at least one of zinc dibenzyl dithiocarbamate (ZBEC), tetrabenzyl thiuram disulfide (TBZTD), and zinc diethyl dithiocarbamate (ZDEC). The lubricant is polyethylene glycol. The foaming agent is selected from at least one of 4,4'-oxybisbenzenesulfonyl hydrazide (OBSH) and azodicarbonamide (AC).
[0032] The preparation steps of the modified red brick powder are as follows: (a) Adding the red brick powder (MBP) from construction waste into a hydrochloric acid solution with a mass concentration of 3% and stirring for 30 minutes, washing with water to remove impurities, calcining at 500-800°C for 2 hours, then washing with water, filtering with an 80-mesh sieve, and drying in an oven at 100°C for 4 hours to obtain a porous red brick powder (P-MBP); (b) adding the obtained porous red brick powder into anhydrous ethanol, and adding silane coupling agent Si-69 at a mass ratio of 1:10 to the porous red brick powder, and then stirring at 80° C. for 1-2 hours, filtering, and obtaining silane-modified red brick powder (Si-MBP); (c) adding the silane-modified red brick powder to a Tris-HCl buffer solution at pH = 8.5, and adding a dopamine solution at a concentration of 2 mg / mL at a rate of 10 mL / g, and stirring for 12 hours to ensure that dopamine self-polymerizes and is coated on the powder surface, thereby obtaining a red brick powder coated with polydopamine (PDA-Si-MBP); (d) A MgAl-LDH suspension with a mass concentration of 2-3% was added to the polydopamine-coated red brick powder at a volume of 3 mL / g, and the mixture was ultrasonically dispersed for 20 min and then filtered. The mixture was then vacuum dried at 80 °C for 4 h to obtain a modified red brick powder (LDH-PDA-Si-MBP).
[0033] The preparation method of the high-performance EPDM rubber foam material comprises the following steps: 1) First, vacuum dry the modified red brick powder at 80-120℃ for 2-4h; 2) Place the EPDM in an open mixer or internal mixer and plasticize at 60-90°C for 3-5 minutes; 3) Add carbon black, light calcium carbonate, zinc oxide, stearic acid, paraffin oil, lubricant and dried modified red brick powder to the plasticized EPDM in sequence, and mix at 80-100°C for 8-12 minutes to evenly disperse the filler; 4) After the materials are fully mixed, cool to 50-70°C, then add accelerator, vulcanizer and foaming agent, and continue mixing at 60-80°C for 5-8 minutes; 5) placing the rubber mixture obtained in step 4) in a two-roll open mill, and performing secondary plastication for 10-15 minutes at 40-60° C., and performing multiple opening and closing operations to remove the gas generated during the mixing process and improve the uniformity of foaming; 6) The rubber mixture obtained in step 5) is placed in a mold, heated to 155°C at a rate of 2-3°C / min, and kept at this temperature for 25 minutes for vulcanization and foaming to obtain a high-performance EPDM rubber foam material.
[0034] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0035] The BET specific surface area of the red brick powder used in the embodiment is 30-80 m / g, and the particle size is controlled at 20-50 μm. The EPDM rubber used is Lanxess Keltan 6950. The carbon black used is Cabot Vulcan N330. The paraffin oil used is Chevron Paralux 6001. The vulcanizing agent used is sulfur. The accelerator used is TBZTD. The lubricant used is polyethylene glycol 2000. The foaming agent used is OBSH. Example
[0036] 1) MBP was added to a 3% hydrochloric acid solution and stirred for 30 minutes, then washed with water to remove impurities, and then calcined at 600°C for 2 hours, then washed with water, filtered with an 80-mesh sieve, and dried in an oven at 100°C for 4 hours to obtain P-MBP; 2) Take P-MBP, add it to anhydrous ethanol, and add a 5% mass concentration of silane coupling agent Si-69 solution according to the mass ratio of P-MBP to Si-69 of 10:1, stir at 80°C for 1 hour, filter, and obtain Si-MBP; 3) Add Si-MBP to a Tris-HCl buffer solution at pH = 8.5, and add 2 mg / mL DA solution at a rate of 10 mL / g, and stir for 12 hours to obtain PDA-Si-MBP; 4) Take PDA-Si-MBP, add MgAI-LDH suspension with a mass concentration of 2% at an amount of 3 mL / g, filter after ultrasonic dispersion for 20 minutes, and vacuum dry at 80°C for 4 hours to obtain LDH-PDA-Si-MBP composite filler; 5) 40 parts by weight of the obtained LDH-PDA-Si-MBP composite filler were vacuum dried at 80° C. for 2 h; 6) Place 100 parts of EPDM in an open mixer or internal mixer and plasticize at 60°C for 5 minutes; 7) Add 6 parts of carbon black, 38 parts of light calcium carbonate, 10 parts of zinc oxide, 2 parts of stearic acid, 15 parts of paraffin oil, 1.5 parts of lubricant and dried LDH-PDA-Si-MBP composite filler to the plasticized EPDM in sequence, and mix at 80°C for 10 minutes to evenly disperse the filler; 8) After the materials are fully mixed, cool to 60°C, then add 1.5 parts of accelerator, 1.0 parts of vulcanizing agent and 5 parts of foaming agent, and continue mixing at 80°C for 5 minutes; 9) placing the rubber mixture obtained in step 8) in a two-roll open mill, and performing secondary plastication at 60° C. for 10 min, and performing multiple opening and closing operations to remove the gas generated during the mixing process; 10) The rubber mixture obtained in step 9) is placed in a mold, heated to 155° C. at a rate of 2° C. / min, kept at this temperature for 25 min, and vulcanized and foamed to obtain a high-performance EPDM rubber foam material.
[0037] Comparative Example 1 1) Place 100 parts of EPDM by weight in an open mixer or internal mixer and plasticize at 60°C for 5 minutes; 2) Add 6 parts of carbon black, 38 parts of light calcium carbonate, 10 parts of zinc oxide, 2 parts of stearic acid, 15 parts of paraffin oil and 1.5 parts of lubricant to the plasticized EPDM in sequence, and mix at 80°C for 10 minutes to evenly disperse the filler; 3) After the materials are fully mixed, cool to 60°C, then add 1.5 parts of accelerator, 1.0 parts of vulcanizing agent and 5 parts of foaming agent, and continue mixing at 80°C for 5 minutes; 4) placing the rubber mixture obtained in step 3) in a two-roll open mill, and performing secondary plastication at 60° C. for 10 min, and performing multiple opening and closing operations to remove the gas generated during the mixing process; 5) The mixed rubber obtained in step 4) is placed in a mold, and the temperature is raised to 155° C. at a rate of 2° C. / min, and kept at this temperature for 25 minutes for vulcanization and foaming to obtain an EPDM rubber foam material.
[0038] Comparative Example 2 1) MBP was added to a 3% hydrochloric acid solution and stirred for 30 minutes, then washed with water to remove impurities, and then calcined at 600°C for 2 hours, then washed with water, filtered with an 80-mesh sieve, and dried in an oven at 100°C for 4 hours to obtain P-MBP; 2) 40 parts by weight of the obtained P-MBP were dried under vacuum at 80°C for 2 h; 3) Place 100 parts of EPDM in an open mixer or internal mixer and plasticize at 60°C for 5 minutes; 4) Add 6 parts of carbon black, 38 parts of light calcium carbonate, 10 parts of zinc oxide, 2 parts of stearic acid, 15 parts of paraffin oil, 1.5 parts of lubricant and dried P-MBP to the plasticized EPDM in sequence, and mix at 80°C for 10 minutes to evenly disperse the filler; 5) After the materials are fully mixed, cool to 60°C, then add 1.5 parts of accelerator, 1.0 parts of vulcanizing agent and 5 parts of foaming agent, and continue mixing at 80°C for 5 minutes; 6) placing the rubber mixture obtained in step 5) in a two-roll open mill, and performing secondary plasticization at 60° C. for 10 min, and performing multiple opening and closing operations to remove the gas generated during the mixing process; 7) The mixed rubber obtained in step 6) is placed in a mold, and the temperature is raised to 155° C. at a rate of 2° C. / min, and kept at this temperature for 25 minutes for vulcanization and foaming to obtain an EPDM rubber foam material.
[0039] Comparative Example 3 1) MBP was added to a 3% hydrochloric acid solution and stirred for 30 minutes, then washed with water to remove impurities, and then calcined at 600°C for 2 hours, then washed with water, filtered with an 80-mesh sieve, and dried in an oven at 100°C for 4 hours to obtain P-MBP; 2) Take P-MBP, add it to anhydrous ethanol, and add a 5% mass concentration of silane coupling agent Si-69 solution according to the mass ratio of P-MBP to Si-69 of 10:1, stir at 80°C for 1 hour, filter, and obtain Si-MBP; 3) 40 parts by weight of the obtained Si-MBP were dried under vacuum at 80°C for 2 h; 4) Place 100 parts of EPDM in an open mixer or internal mixer and plasticize at 60°C for 5 minutes; 5) Add 6 parts of carbon black, 38 parts of light calcium carbonate, 10 parts of zinc oxide, 2 parts of stearic acid, 15 parts of paraffin oil, 1.5 parts of lubricant and dried Si-MBP to the plasticized EPDM in sequence, and mix at 80°C for 10 minutes to evenly disperse the filler; 6) After the materials are fully mixed, cool to 60°C, then add 1.5 parts of accelerator, 1.0 parts of vulcanizing agent and 5 parts of foaming agent, and continue mixing at 80°C for 5 minutes; 7) placing the rubber mixture obtained in step 6) in a two-roll open mill, and performing secondary plastication at 60° C. for 10 min, and performing multiple opening and closing operations to remove the gas generated during the mixing process; 8) The mixed rubber obtained in step 7) is placed in a mold, heated to 155° C. at a rate of 2° C. / min, kept at this temperature for 25 min, and vulcanized and foamed to obtain an EPDM rubber foam material.
[0040] Comparative Example 4 1) MBP was added to a 3% hydrochloric acid solution and stirred for 30 minutes, then washed with water to remove impurities, and then calcined at 600°C for 2 hours, then washed with water, filtered with an 80-mesh sieve, and dried in an oven at 100°C for 4 hours to obtain P-MBP; 2) Take P-MBP, add it to anhydrous ethanol, and add a 5% mass concentration of silane coupling agent Si-69 solution according to the mass ratio of P-MBP to Si-69 of 10:1, stir at 80°C for 1 hour, filter, and obtain Si-MBP; 3) Add Si-MBP to a Tris-HCl buffer solution at pH = 8.5, and add 2 mg / mL DA solution at a rate of 10 mL / g, stir for 12 hours, and filter to obtain PDA-Si-MBP; 4) 40 parts by weight of the obtained PDA-Si-MBP were dried under vacuum at 80° C. for 2 h; 5) Place 100 parts of EPDM in an open mixer or internal mixer and plasticize at 60°C for 5 minutes; 6) Add 6 parts of carbon black, 38 parts of light calcium carbonate, 10 parts of zinc oxide, 2 parts of stearic acid, 15 parts of paraffin oil, 1.5 parts of lubricant and dried PDA-Si-MBP to the plasticized EPDM in sequence, and mix at 80°C for 10 minutes to evenly disperse the filler; 7) After the materials are fully mixed, cool to 60°C, then add 1.5 parts of accelerator, 1.0 parts of vulcanizer and 5 parts of foaming agent, and continue mixing at 80°C for 5 minutes; 8) placing the rubber mixture obtained in step 7) in a two-roll open mill, and performing secondary plastication at 60° C. for 10 min, and performing multiple opening and closing operations to remove the gas generated during the mixing process; 9) The mixed rubber obtained in step 8) is placed in a mold, heated to 155° C. at a rate of 2° C. / min, kept at this temperature for 25 min, and vulcanized and foamed to obtain an EPDM rubber foam material.
[0041] Comparative Example 5 1) MBP was added to a 3% hydrochloric acid solution and stirred for 30 minutes, then washed with water to remove impurities, and then calcined at 600°C for 2 hours, then washed with water, filtered with an 80-mesh sieve, and dried in an oven at 100°C for 4 hours to obtain P-MBP; 2) Take P-MBP, add it to anhydrous ethanol, and add a 5% mass concentration of silane coupling agent Si-69 solution according to the mass ratio of P-MBP to Si-69 of 10:1, stir at 80°C for 1 hour, filter, and obtain Si-MBP; 3) Add Si-MBP to a Tris-HCl buffer solution at pH = 8.5, and add 2 mg / mL DA solution at a rate of 10 mL / g, stir for 12 hours, and filter to obtain PDA-Si-MBP; 4) 40 parts by weight of the obtained PDA-Si-MBP were dried under vacuum at 80° C. for 2 h; 5) Place 100 parts of EPDM in an open mixer or internal mixer and plasticize at 60°C for 5 minutes; 6) Add 6 parts of carbon black, 38 parts of light calcium carbonate, 10 parts of zinc oxide, 2 parts of stearic acid, 15 parts of paraffin oil, 1.5 parts of lubricant, 4 parts of MgAl-LDH and dried PDA-Si-MBP to the plasticized EPDM in sequence, and mix at 80°C for 10 minutes to evenly disperse the filler; 7) After the materials are fully mixed, cool to 60°C, then add 1.5 parts of accelerator, 1.0 parts of vulcanizer and 5 parts of foaming agent, and continue mixing at 80°C for 5 minutes; 8) placing the rubber mixture obtained in step 7) in a two-roll open mill, and performing secondary plastication at 60° C. for 10 min, and performing multiple opening and closing operations to remove the gas generated during the mixing process; 9) The mixed rubber obtained in step 8) is placed in a mold, heated to 155° C. at a rate of 2° C. / min, kept at this temperature for 25 min, and vulcanized and foamed to obtain an EPDM rubber foam material.
[0042] Table 1 Comparison of properties of EPDM rubber foam materials prepared in Examples and Comparative Examples
[0043] According to the data in Table 1, the EPDM foam material prepared by the embodiment using the LDH-PDA-Si-MBP composite filler showed significant improvements in mechanical properties, flame retardant properties, thermal stability and cell uniformity. Compared with the EPDM foam material prepared in the comparative example, the tensile strength of the EPDM foam material obtained in the embodiment increased by 19.4%~38.9% (up to 12.5 MPa), the tear strength increased by 13.3%~37.8% (up to 6.2 kN / m), and the elongation at break remained at about 450%, showing excellent flexibility and durability. At the same time, the cell uniformity was increased to more than 95%, which effectively improved the uniformity of the foaming structure and enhanced the dimensional stability of the material. The oxygen index (LOI) reached a maximum of 31.2%, which was 5.2%~9.5% higher than the comparative example, significantly enhancing the flame retardant properties. The heat release rate (HRR) was reduced by 9.1%~38.6%, which effectively reduced the heat release during the combustion process and can meet the application fields such as rail transit and automotive seals with high flame retardant requirements. The thermal decomposition temperature (TGA) increased by 14.3%~21.4%, up to 340°C, which significantly improved the heat resistance of the material. Overall, the EPDM foam material of the embodiment showed excellent performance in multiple performance indicators, which fully demonstrated the modification effect of the LDH-PDA-Si-MBP composite filler.
[0044] In conclusion, the present invention achieves comprehensive optimization of the EPDM foam material in terms of mechanical properties, flame retardancy, pore structure stability and wear resistance through multiple modifications of fillers and optimized foaming and vulcanization process, and has important industrial application value and broad market prospects.
[0045] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A high-performance EPDM rubber foam material based on modified red brick powder, characterized in that: The material is prepared from the following raw materials in parts by weight: 100 parts of EPDM rubber, Carbon black 10-40 parts, 40 parts of modified red brick powder, 30-50 parts of light calcium carbonate, 10-20 parts of paraffin oil, Zinc oxide 5-15 parts, Vulcanizing agent 0.5-3 parts, Accelerator 0.5-2 parts, 1-5 parts of stearic acid, Lubricant 0.5-3 parts, 5-15 parts of foaming agent.
2. The high performance EPDM rubber foam material according to claim 1, characterized in that: The preparation steps of the modified red brick powder are as follows: (a) adding red brick powder to a hydrochloric acid solution with a mass concentration of 3% and stirring for 30 minutes, washing with water to remove impurities, calcining at 500-800°C for 2 hours, then washing with water, filtering and drying to obtain porous red brick powder; (b) adding the porous red brick powder into anhydrous ethanol and adding a silane coupling agent Si-69, stirring at 80° C. for 1-2 hours, filtering, and obtaining a silane-modified red brick powder; (c) adding the obtained silane-modified red brick powder into a Tris-HCl buffer solution at pH=8.5, adding a 2 mg / mL dopamine solution and stirring for 12 hours to obtain a red brick powder coated with polydopamine; (d) The obtained red brick powder coated with polydopamine is added to a MgAl-LDH suspension with a mass concentration of 2-3%, filtered after ultrasonic dispersion, and vacuum dried at 80° C. for 4 hours to obtain the modified red brick powder.
3. The high performance EPDM rubber foam material according to claim 2, characterized in that: The mass ratio of the porous red brick powder to the silane coupling agent Si-69 used in step (b) is 10:1; In step (c), the amount of dopamine solution is 10 mL per gram of silane-modified red brick powder; In step (d), 3 mL of MgAl-LDH suspension is added per gram of red brick powder coated with polydopamine.
4. The high performance EPDM rubber foam material according to claim 1, characterized in that: The vulcanizing agent is selected from at least one of sulfur and BIBP.
5. The high performance EPDM rubber foam material according to claim 1, characterized in that: The accelerator is selected from at least one of zinc dibenzyl dithiocarbamate, tetrabenzylthiuram disulfide, and zinc diethyl dithiocarbamate.
6. The high performance EPDM rubber foam material according to claim 1, characterized in that: The lubricant is polyethylene glycol.
7. The high performance EPDM rubber foam material according to claim 1, characterized in that: The foaming agent is selected from at least one of 4,4'-oxybisbenzenesulfonyl hydrazide and azodicarbonamide.
8. A method for preparing a high-performance EPDM rubber foam material as claimed in claim 1, characterized in that: The following steps are involved: 1) First, vacuum dry the modified red brick powder at 80-120℃ for 2-4h; 2) Plasticize EPDM at 60-90℃ for 3-5min; 3) Add carbon black, light calcium carbonate, zinc oxide, stearic acid, paraffin oil, lubricant and dried modified red brick powder to the plasticized EPDM in sequence, and mix at 80-100°C for 8-12 minutes; 4) After the materials are fully mixed, cool to 50-70°C, then add accelerator, vulcanizer and foaming agent, and continue mixing at 60-80°C for 5-8 minutes; 5) The mixed rubber obtained in step 4) is subjected to secondary plasticizing, and then vulcanized and foamed to obtain the high-performance EPDM rubber foam material.
9. The method for preparing a high-performance EPDM rubber foam material according to claim 8, characterized in that: The temperature of the secondary mastication is 40-60°C and the time is 10-15 minutes.
10. The method for preparing a high-performance EPDM rubber foam material according to claim 8, characterized in that: The vulcanization foaming is carried out in a gradual heating manner, with a heating rate of 2-3°C / min, heating to 155°C and keeping the temperature for 25 minutes.
Citation Information
Patent Citations
Silicone rubber sealing gasket resistant to high-temperature water vapor and preparation method thereof
CN105860532A
Environment-friendly rubber composite material of polydopamine / KH550 modified carbon nanotube and preparation method of environment-friendly rubber composite material
CN119081412A
Glass fiber reinforced nylon composite material and preparation method thereof
CN119192832A
Rubber filler, rubber composite material containing same, preparation method therefor, and use thereof
WO2024255096A1
Cited By
Freeze-thaw-resistant and salt-corrosion-resistant polymer modified EPDM safety brick and preparation method thereof
CN121021990A
Modified ethylene propylene rubber composite material for high-speed train cable terminal as well as preparation method and application thereof
CN121736416A
Modified ethylene-propylene rubber composite material for high-speed train cable terminal and preparation method and use thereof
CN121736416B